Constructing maternal responsibility: narratives of “motherly love” and maternal blame in epigenetics research - Courtney McMahon (New Genetics and Society)
Research in epigenetics is demonstrating the importance of maternal care towards offspring early in life for long-term health and behavioral outcomes. Although most of this research has been conducted in rodents, these findings are increasingly framing broader debates about mothers’ moral responsibilities for the health of their offspring. In this paper, I investigate the implications of scientific narratives and research agendas of maternal care for current discourses surrounding maternal epigenetic responsibility. I show how despite clear differences between rodent and human contexts of care, researchers tend to construct rodent maternal care as a form of love or emotional commitment. This construction, which ignores fathers’ care for their offspring, reflects widespread social assumptions about mothers’ particular or “natural” capacities to love their children. This has important implications for how we assign moral blame. Because love is important to our widespread understandings of parental virtues, mothers who act “unlovingly” are prone to being judged in an especially harsh manner. By embedding simplistic and gendered assumptions about mothers’ love for their children, then, epigenetics research perpetuates the tendency to consider mothers especially blameworthy where they are perceived as failing to sufficiently care for or love their children.